What ‘unexplored’ means: mapping regions with digitized natural history records to look for ‘biodiversity blindspots’ - Ball, Laymon; Rodríguez-Machado, Sheila; Paredes-Burneo, Diego; Rutledge, Samantha; Boyd, David A.; Vander Pluym, David; Babb-Biernacki, Spenser; Chipps, Austin S.; Öztürk, Rafet Ç.; Terzi, Yahya; Chakrabarty, Prosanta (PeerJ, 2025)
We examined global records of accessible natural history voucher collections (with publicly available data and reliable locality data) for terrestrial and freshwater vascular plants, fungi, freshwater fishes, birds, mammals, and herpetofauna (amphibians and reptiles) and highlight areas of the world that would be considered undersampled and sometimes called ‘unexplored’ (i.e., have relatively low, or no evidence of, past sampling efforts) under typical Western-scientific descriptions. We also question what ‘unexplored’ may mean in these contexts and explain how replacing the term in favor of more nuanced phrasing (e.g., ‘biodiversity blindspots,’ which emphasizes the lack of publicly available data about specimens) can mitigate future misunderstandings of natural history science. We also highlight geographic regions where there are relatively few or no publicly available natural history records to raise awareness about habitats that might be worthy of future natural history research and conservation. A major finding is that many of the areas that appear ‘unexplored’ may be in countries whose collections are not digitized (i.e., they don’t have metadata such as GPS coordinates about their voucher specimens publicly available). We call for museums to prioritize digitizing those collections from these ‘biodiversity blindspots’ and for increased funding for museums to aid in these efforts. We also argue for increased scientific infrastructure so that more reference collections with vouchers can be kept in the countries of origin (particularly those countries lacking such infrastructure currently).
Keywords: Biodiversity; Vouchers; Museums; Digitization; Collections; GBIF